Fabricating Suspended Carbon Wires Using SU-8 Photolithography. (27th April 2016) - Giogli, Emanuele; Islam, Monsur; Martinez-Duarte, Rodrigo
Abstract : We present initial results towards the fabrication of suspended structures between photo-patterned high aspect ratio SU-8 posts as precursors for carbon wires and bridges. Initial results show that carbon wires of diameter as low as 800 nm can be formed. SU-8 is an epoxy-based negative photoresist, commonly used as high quality carbon precursor in carbon MEMS technology. This work has two main goals: 1) characterize the formation of suspended structures between SU-8 posts depending on the photolithography exposure setup and time of the exposure, the shape and size of the anchors and the gap between them; and 2) examine the shrinkage during carbonization. The suspended structures were characterized using optical and electron microscopy. Future work is to extend the characterization to wafers with different aspect ratio, and different types of mask contact during the exposure of the photoresist.